PROBLEM OF FUTURE SPECIALIST'S PROFESSIONAL INTERACTION THROUGH DEONTOLOGY PRISM - О. Bratkova (Borys Grinchenko Kyiv Metropolitan University, 2017)
The analysis of scientific sources reveals the nature and the content of the key research concepts, determines functions and the role of ethics in future specialist's professional interaction, clarifies the basic moral and ethical rules of professional interaction and communication as well as the factors that complicate this process and measures aimed at overcoming destructive professional interaction. Professionalism is the set of theoretical knowledge, practical experience and professional skills gained in a certain labour division in the sphere of human activity. As for profession, it's a willingness to perform socially purposeful activity that transforms the world and reveals personality's creative, intellectual and spiritual potential. Concerning the term "interaction", it is a process of direct or indirect influence of communicating subjects on each other, which leads to their actions and interconnection. As for professional interaction, it is a purposeful, socially conditioned, dynamic process of direct or indirect simultaneous influence of each other on the result of certain professional activity, under the steering role of the subject, which has a set of theoretical and practical training, which aims to realize the content of professional activity and meet the needs of one another. The term "deontology" is derived from the Greek (Δέον -"duty" and "logos" -science) - a chapter of ethics which studies the problems of duty. And professional ethics is primarily a certain profession specific code of ethics of people of certain profession. The main function of professional ethics is to regulate the moral relations of people in one of the main areas of social life - work activity (material-productive, economic, administrative, spiritual, and cultural). The main moral and ethical standards that promote effective professional interaction and communication are the following: honesty, integrity, fairness, tolerance, respect, responsibility, etc. The factors which complicate the process of professional interaction and lead to negative consequences are the following: communication barriers (intellectual, emotional, esthetic, moral, motivational and cultural prejudice barriers), subjects' interaction mistakes (stereotypical thinking and behaviour), neglect or ignorance of professional ethics (indifference, negligence, defamation, abuse of his official position, etc.). Therefore, to achieve success in overcoming this problem, there should be a set of interrelated mechanisms, which include strong and stable infrastructure of ensuring ethics, specific preventive methods of such negative behaviour and effective application of the law.